Saúde do trabalhador na odontologia: o cirurgião-dentista em foco - Saliba, Nemre Adas [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Prado, Rosana Leal do [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2013)
Objective: To assess characteristics associated with the work and health of dentists graduated from Brazilian public universities. Methods: Professionals graduated from the Dental School of Araçatuba, UNESP, Brazil between 2000 and 2010 took part in this study. A form was sent by post or e-mail containing 36 questions on the following variables: population of the city where they work, sociodemographic data, declared monthly income, health complaints, physical activity and level of satisfaction with the profession. Associations between the variables were verified by the chi-square test. Results: There was a prevalence of females (65.6%). Most participants worked in cities with over 500,000 inhabitants (31.7%). Health and stress complaints were expressed by 67.0% and 60.3%, respectively. The prevalent health complaint was backache (81.2%) and the most frequent stress symptom was excessive irritability (57.4%). The main cause of stress was the excess of activities (60.4%). Stress was significantly associated with the number of working hours, year of graduation and professional satisfaction (p<0.05). Health complaints were significantly associated with professional satisfaction (p<0.05). No physical activity was reported by 39.2% of the participants. Conclusion: It could be observed feminization of dentistry and a large number of professionals working in large-size cities. Many weekly working hours and time since graduation were associated with stress. Professional satisfaction was associated with health complaints and stress.

Objetivo: Verificar características ligadas ao trabalho e à saúde do cirurgião-dentista egresso de universidade pública brasileira. Método: Participaram do estudo profissionais egressos de Faculdade de Odontologia de Araçatuba, São Paulo, Brasil, no período entre 2000 e 2010. Foi enviado pelo correio e/ou e-mail um instrumento composto por 36 questões, contendo as variáveis como porte populacional da cidade em que desempenham suas atividades profissionais, dados sociodemográficos, remuneração declarada, queixas de saúde, prática de atividade física e satisfação em relação à profissão. Utilizou-se o teste Qui-quadrado para verificação de associação entre variáveis. Resultados: O gênero feminino representou 65,6% dos participantes. Atuavam em cidades com mais de 500 mil habitantes, 31,7%. Foram relatadas queixas de saúde e estresse por 67,0% e 60,3%, respectivamente. A queixa prevalente foi dores nas costas (81,2%) e o sintoma de estresse, irritabilidade excessiva (57,4%). O principal motivo de estresse foi excesso de atividades 60,4%. O estresse mostrou associação com o número de horas de trabalho, ano de formatura e satisfação profissional (p<0,05). As queixas de saúde estiveram associadas à satisfação profissional (p<0,05). Não realizavam atividade física 39,2%. Conclusão: A feminilização da odontologia pôde ser constatada e também foi alto o número de profissionais que atuava em cidades de grande porte. As horas semanais de trabalho e o tempo de formado estiveram associados ao sentimento de estresse. A satisfação profissional mostrou associação em relação à presença de queixas de saúde e estresse.
Worker’s health in dentistry: focusing on the dentist
Keywords: Dentistry; Occupational health; Occupational dentistry; Stress psychological; Odontologia; Saúde do trabalhador; Odontologia do trabalho; Estresse psicológico